2010
DOI: 10.3892/ijmm_00000355
|View full text |Cite
|
Sign up to set email alerts
|

Specific microRNA expression during chondrogenesis of human mesenchymal stem cells

Abstract: Abstract. Mesenchymal stem cells (MSCs) have the capacity to self-renew and differentiate into multiple cell types, but little is known about the precise mechanism of this procedure. Recent studies show that a group of short noncoding RNAs called microRNAs (miRNAs) play a key role in this procedure. However, little work has been done to determine the miRNAs which specifically regulate the differentiation of MSCs. In this study, we cultured human MSCs and chondrogenic differentiation MSCs of 3 donors, and inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Simultaneously, the iNOS gene suppression by miR‐193b‐3p was detected in this study; however, neither TNF‐α nor iNOS was proven to precisely regulate—miR‐193b‐3p as its target. Recent studies have reported that miR‐193b‐3p was overexpressed during chondrogenesis of human adipose‐derived stem cells and human bone marrow‐derived mesenchymal stem cells, and regulated early chondrogenic differentiation with the help of TGFBR2 and TGFBR3 . Yet, the TGF‐β signaling pathway, regulated by miR‐193b‐3p, appears to play a more essential role in both chondrocyte differentiation and osteoarthritis development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the iNOS gene suppression by miR‐193b‐3p was detected in this study; however, neither TNF‐α nor iNOS was proven to precisely regulate—miR‐193b‐3p as its target. Recent studies have reported that miR‐193b‐3p was overexpressed during chondrogenesis of human adipose‐derived stem cells and human bone marrow‐derived mesenchymal stem cells, and regulated early chondrogenic differentiation with the help of TGFBR2 and TGFBR3 . Yet, the TGF‐β signaling pathway, regulated by miR‐193b‐3p, appears to play a more essential role in both chondrocyte differentiation and osteoarthritis development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to hsa-miR-130b-3p, there is still a lack of evidence concerning the action of it in relation to pain conditions, but established is its involvement at different levels in the pathophysiology of several types of tumors 94,282 . Moreover, the dysregulation of this miRNA has been associated to several pathological conditions such as obesity, or resistance to insulin, but has been also found involved in physiological process which includes osteo and chondrogenesis 101,169,171 . In Study II the results find hsa-miR-130b-3p positively dysregulated in the preoperative circulation of KOA patients with bad postoperative recovery, but more evidence is necessary to validate the involvement of this miRNA for post-operative pain conditions in patients with KOA and show whether it can serve as a potential biomarker (Study II).…”
Section: Second Mirna Found Upregulated In Study II Was Hsa-mir-145-5...mentioning
confidence: 99%